Paradoxes in Borderline Emotional Dysregulation in Adolescence: Influence of Parenting, Stressful Life Events, and Attachment - Marion Robin; Marion Robin; Jean Belbèze; Alexandra Pham-Scottez; Gérard Shadili; Victoire Peres; Jérôme Silva; Maurice Corcos; Maurice Corcos; Mario Speranza; Mario Speranza (Frontiers in Psychiatry, 2021)
Introduction: Borderline personality disorder (BPD) in adolescents is characterized by emotional dysregulation, insecure attachment, a history of stressful life events (SLEs) as well as dysfunctional parent–child interactions. The respective contribution of each of these factors on BPD affective symptoms is not yet clear. The purpose of this study is to assess the distinct impact of parental adversity and SLEs on BPD affective symptoms and the role of attachment and alexithymia in such emotional processes.Method: This study explored parental dysfunction and SLEs as predictors of affective symptoms of BPD and of attachment insecurity in BPD adolescents (n = 85) and healthy controls (n = 84) aged 13–19 years from the European Research Network on BPD. The links between adversity and BPD symptoms were also investigated by emotional dysregulation assessment, as measured by alexithymia and hopelessness.Results: Dysfunctional parental interactions were linked to affective symptoms, hopelessness, and anxious attachment in healthy controls but not in BPD. Cumulative SLEs were positively correlated with affective symptoms and avoidant attachment in the control group but negatively correlated with both these variables in BPD. Multivariate regression analysis revealed that, in BPD, affective symptoms were independent of dysfunctional parenting but depended on attachment, whereas in controls, a maternal affectionless control style directly predicted affective symptoms. Moreover, increasing numbers of SLEs reduced affective symptoms in BPD, independently of parental interactions or attachment, and were associated with growing use of operative thinking.Discussion: BPD patients showed paradoxical emotional reactions: there was no increase of hopelessness and affective symptoms with an increased parental dysfunction, but a decrease in affective symptoms and hopelessness with cumulative SLE. Two pathways arose, one involving attachment as an emotional dysregulation process for parent–child interactions and a second one for SLE, with a more direct pathway to affective symptoms, independent of attachment but dependent on early interactions, and involving alexithymia. In summary, adversity factors have distinct effects in BPD, and attachment is partly accountable for affective symptoms independently of adversity. Our results suggest that in highly insecure conditions, cumulative adversity may produce paradoxical effects, including a lesser expression of affective symptoms and hopelessness.